2010
DOI: 10.3168/jds.2008-1864
|View full text |Cite
|
Sign up to set email alerts
|

Pressure distribution at the teat–liner and teat–calf interfaces

Abstract: During milking, the teat is loaded because of a combination of vacuum and pressure of the collapsing liner. It is assumed that pressure concentrations tend to cause teat-end injuries and hyperkeratosis. The pressure distribution on the bovine teat was measured to test the hypothesis that the pressures of the collapsed liner are unevenly distributed over the teat. With the aid of a pressure-sensitive sensor (approximately 2 gauge points/cm(2)), the pressures at the teat-liner and the teat-calf interfaces were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 6 publications
4
12
2
1
Order By: Relevance
“…These results agree with those of Tol, Schrader and Aernouts [15]. They had found that the maximum pressure was always exerted on the teat end.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results agree with those of Tol, Schrader and Aernouts [15]. They had found that the maximum pressure was always exerted on the teat end.…”
Section: Discussionsupporting
confidence: 92%
“…Davis, Reinemann and Mein [14] detected pressures of 20–41 kPa between the liner and teat. The artificial teats used in the present investigation could explain why the pressure values measured in this investigation are higher: in the other investigations the artificial teats were hollow and made of silicone [15]; our artificial teats were not hollow. However, the silicone teat used in the present investigation was very stiff.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Davis et al [13] measured the compressive load applied to the teat by the closed liner using an artificial teat equipped with a miniature load cell and found that the compressive load of a liner is proportional to the thickness of the liner wall; the authors determined a curvilinear relationship between the insertion depth and the compressive teat load as well. Tol et al [14] investigated the teat-liner interface using a flexible pressure-sensitive layer and found that conventional round liners concentrated the load over two sides of the end of the teat. In contrast, liners with softer material, reduced tension, a smaller barrel, and reduced mouthpiece depth distributed the pressure over a larger area of the teat, but the maximum pressure was always exerted at the teat end.…”
Section: Introductionmentioning
confidence: 99%